O beato franciscano : messianismo religioso em Alagoas - Neves, Gilvan Gomes das (2014)
This present research has as its study object a devotee from the state of Alagoas, called Antonio Fernandes Amorim, "The Franciscan Devotee. His appearing, in 1936, in the Alagoas hinterland happened soon after the death of the priest Cícero Romão Batista, in Ceará. It is intended to cover his pilgrimage until he settled in Serra Grande, in the municipality of Quebrangulo - Alagoas, where a settlement soon appeared around him;the political and religious persecution he suffered; the way he fits in the traditional messianic-religious in the northeast of Brazil, its similarities and differences. It is intended, as well, to discuss the succession of his leading position in the religious community created around him; on 30th of July 1954 he was assassinated and after his death, the church intervenes in Serra Grande Village and the Capuchins Friars take over the direction of both the orphanage and the chapel. To obtain the data, there were used bibliographical research, documental analysis, as well as, interviews with local people, who witnessed the facts researched.